Examining How Conditioning on Different Wave Lengths Alters Sample Characteristics and Results in a Panel Dataset of Youth Who Have Committed Serious Offenses - Kijowski, Matthew C. (Journal of developmental and life-course criminology, 2022)
Research on missing data in panel datasets has focused on attrition where respondents drop out and do not return. An equally important, but understudied, form of missing data include missed interviews where respondents contribute different number of total interviews to a panel dataset. Because individuals with crime-related characteristics miss more interviews, conditioning one’s sample on different number of waves changes the composition of the sample, and likely the subsequent conclusions. Scholars must weigh the balancing act of wanting a sample with more waves of data to tease out their panel process against the concern that they will lose individuals sensitive to the process under study by requiring too many waves of data. Using the Pathways to Desistance study, a panel dataset of youth who have committed serious offenses, we compared sample characteristics across multiple conditioned samples to unpack how the characteristics of one’s sample changes as more waves are required to be entered into the sample. We further demonstrate the implications of this in an applied setting by examining the relationship between residential mobility and perceptions of informal social costs. Our results indicate that the characteristics of one’s panel sample are sensitive to the number of waves one conditions their sample upon. This is especially prevalent for offending where those who contribute fewer waves of data consistently report higher levels of offending. In our empirical demonstration, substantive conclusions change across conditioned samples. Our study provides unique insight into an understudied phenomenon while also providing practical advice to panel dataset scholars.